2021
DOI: 10.1172/jci.insight.143606
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous allogeneic umbilical cord blood–derived mesenchymal stem cell therapy in recessive dystrophic epidermolysis bullosa patients

Abstract: BACKGROUND Recessive dystrophic epidermolysis bullosa (RDEB) is an incurable disease that causes severe mucocutaneous fragility due to mutations in COL7A1 (encoding type VII collagen [C7]). In this phase I/IIa trial, we evaluated the safety and possible clinical efficacy of intravenous infusion of allogeneic human umbilical cord blood–derived mesenchymal stem cells (hUCB-MSCs) in patients with RDEB. METHODS Four adult and two pediatric patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The present study also revealed that cells isolated from PBMCs using the Human Mesenchymal Stem Cell Enrichment Cocktail express type VII collagen and positive selection markers for MSCs (CD45 and CD34), suggesting that small numbers of MSCs or mesenchymal stromal cells that express type VII collagen are circulating in the peripheral blood. Although the actual function of type VII collagen-expressing MSCs and/or mesenchymal stromal cells remain unclear, it has been reported that locally injected or intravenously administered MSCs are associated with clinical improvement in patients with RDEB, with the transient restoration of type VII collagen at the basal membrane zone [16,[18][19][20][21]. These findings also support our results that MSCs can express type VII collagen.…”
Section: Discussionsupporting
confidence: 91%
“…The present study also revealed that cells isolated from PBMCs using the Human Mesenchymal Stem Cell Enrichment Cocktail express type VII collagen and positive selection markers for MSCs (CD45 and CD34), suggesting that small numbers of MSCs or mesenchymal stromal cells that express type VII collagen are circulating in the peripheral blood. Although the actual function of type VII collagen-expressing MSCs and/or mesenchymal stromal cells remain unclear, it has been reported that locally injected or intravenously administered MSCs are associated with clinical improvement in patients with RDEB, with the transient restoration of type VII collagen at the basal membrane zone [16,[18][19][20][21]. These findings also support our results that MSCs can express type VII collagen.…”
Section: Discussionsupporting
confidence: 91%
“…Among other immune-modulating strategies to treat RDEB, including small-molecule agents (11) and hematopoietic progenitor cell transplantation (28), systemic administration of allogeneic mesenchymal stem cells (MSCs) has emerged as a potential, comparatively well tolerated treatment option (29)(30)(31)(32)(33). Transplanted MSCs migrate to injured tissue sites (such as RDEB skin (34,35)), where they can adaptively respond to biological signals associated with inflammation and injury (36).…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous infusions of allogeneic MSCs from adipose tissue and umbilical cord have also been assessed in a small number of RDEB patients [99,100]. As seen in earlier trials, reduced inflammation and improved wound healing were noted.…”
Section: Mesenchymal Stem/stromal Cellsmentioning
confidence: 94%